Targeting Telomerase with an HLA Class II-Restricted TCR for Cancer Immunotherapy - Dillard, Pierre (Mol Ther, 2021)
T cell receptor (TCR)-engineered T cell therapy is a promising cancer treatment approach. Human telomerase reverse transcriptase (hTERT) is overexpressed in the majority of tumors and a potential target for adoptive cell therapy. We isolated a novel hTERT-specific TCR sequence, named Radium-4, from a clinically responding pancreatic cancer patient vaccinated with a long hTERT peptide. Radium-4 TCR-redirected primary CD4(+) and CD8(+) T cells demonstrated in vitro efficacy, producing inflammatory cytokines and killing hTERT(+) melanoma cells in both 2D and 3D settings, as well as malignant, patient-derived ascites cells. Importantly, T cells expressing Radium-4 TCR displayed no toxicity against bone marrow stem cells or mature hematopoietic cells. Notably, Radium-4 TCR(+) T cells also significantly reduced tumor growth and improved survival in a xenograft mouse model. Since hTERT is a universal cancer antigen, and the very frequently expressed HLA class II molecules presenting the hTERT peptide to this TCR provide a very high (>75%) population coverage, this TCR represents an attractive candidate for immunotherapy of solid tumors.